Molecular cloning, nucleotide sequence, and characterization of lppB, encoding an antigenic 40-kilodalton lipoprotein of Haemophilus somnus. - Theisen, M (1993)
Haemophilus somnus is a facultative intracellular pathogen which causes a wide range of diseases in cattle. To identify putative virulence determinants, a genomic library of H. somnus in Escherichia coli was screened for Congo red binding, a property associated with virulence in pathogenic bacteria, and subsequently with bovine hyperimmune sera raised against H. somnus HS25. A Congo red-binding clone carrying a 1.8-kb DNA insert was found to encode a strongly seroreactive LppB protein with an apparent molecular weight of 40,000. The nucleotide sequence of the entire DNA insert was determined. Two open reading frames coding for polypeptides with calculated molecular weights of 21,893 and 30,721 were identified. The larger open reading frame encoded LppB, while the smaller reading frame encoded a nonseroreactive protein with a relative molecular mass of approximately 18 kDa. The 16 amino-terminal amino acids of the deduced LppB polypeptide showed strong sequence homology to the signal peptide of secreted bacterial proteins, and the sequence Leu-Ala-Ala-Cys at the putative cleavage site corresponds to the consensus cleavage sequence of bacterial lipoproteins. Synthesis of the mature LppB lipoprotein in H. somnus was inhibited by globomycin, a specific inhibitor of signal peptidase II. LppB was localized to the outer membrane of H. somnus.